The Effect of Coping on the Relationship between Work-Family Conflict and Stress, Anxiety, and Depression - Sousa, Cristina (2024)
The challenges experienced in the context of the pandemic have required a significant reconciliation between work and family domains due to confinement and the need to spend more time at home, which may have increased the levels of stress, anxiety, and depression, making it necessary to use resilient coping strategies to overcome the difficulties felt. This study examined the effect of resilient coping on the relationship between work-family conflict and stress, anxiety, and depression in this context. Data were collected using a self-report protocol from a sample of Portuguese workers (N = 476). The results indicated that work-family conflict was positively associated with stress, anxiety, and depression. Resilient coping established a negative relationship with stress, anxiety, and de-pression. The moderation effect was not corroborated; it was found that in the presence of the moderating variable (resilient coping), the relationship between the variables of work-family conflict and stress, anxiety, and depression was strengthened. This study reinforces the importance of ap-propriate interventions in resilient coping in the work-family context, which helps control stress, anxiety, and resilience levels.